Positive psychotic symptoms as a marker of clinical severity in a transdiagnostic sample of help-seeking adolescents - Kaeser, Janko M.; Lerch, Stefan; Sele, Silvano; Reichl, Corinna; Koenig, Julian; Mürner-Lavanchy, Ines M.; Berger, Thomas; Kaess, Michael; Cavelti, Marialuisa (European child & adolescent psychiatry, 2024)
The present study aimed to examine the association between the presence, number, and type of positive psychotic symptoms (PPS) and clinical severity in adolescent patients. Five hundred-six patients aged 11-17 years were assigned to either the noPPS (n = 341), the delusional beliefs only (del; n = 32), the hallucinations only (hall; n = 80), or the delusional beliefs and hallucinations (del&hall; n = 53) group. Generalized Structural Equation Modeling was applied to identify the best-fitting model representing clinical severity indicated by psychiatric diagnoses, depressivity, personality pathology, non-suicidal self-injury, suicide attempts, perceived stress, and psychosocial impairments, assessed by interviews and questionnaires. The groups were compared concerning the final model’s factors. The final model consisted of three factors representing psychopathology and functional impairments, self-harming behavior, and perceived stress (BIC difference to reference model: 103.99). Participants with any PPS scored higher on all factors than the noPPS group (differences in SD: 0.49-1.48). Additionally, the del&hall group scored 1.31 SD higher on psychopathology and functional impairments than the hall group, and 1.16 SD higher on self-harming behavior compared to the del group. Finally, the hall group scored 0.84 SD higher on self-harming behavior than the del group, with no group differences in the other factors. In adolescent patients, the presence of PPS may represent a marker for a more severe form of mental disorder, with hallucinations being indicative of self-harming behavior. Early transdiagnostic assessment of PPS seems indicated as it may inform treatment in the context of clinical staging.